Public concerns over presumed metal and radionuclide pollution: testing a possible link to ovine hepatic melanosis in South Greenland - Violeta Hansen; Ole Lerberg Nielsen; Anders Mosbech; Sandra Drewes Fabricius; Christian Sonne; Jens Søndergaard; Daniel Spelling Clausen; Kasper Lambert Johansen; Floris van Beest; Páll Skúli Leifsson; Heidi Larsen Enemark (Environmental Monitoring and Assessment, 2026)
In South Greenland, public concerns have linked “black livers” in sheep to presumed environmental pollution from the Kvanefjeld mining exploration project. Elevated concentrations of metals and radionuclides in the area reflect natural geochemistry and weathering processes, not pollution from exploration activities. However, in response, we conducted a preliminary case–control study to diagnose the condition, investigate links between liver discoloration and environmental concentrations of metals and radionuclides, and to estimate the annual effective dose to the public from polonium-210 ( 210 Po) ingestion via sheep and lamb liver consumption. We also evaluated the prevalence of acquired melanosis, grazing and herd effects, and their association with carcass quality and disease markers. Histological analysis confirmed acquired melanosis in affected liver samples. No statistically significant differences in concentrations of chemical elements or radionuclides (including 21 0 Po and 21 0 Pb) were found between case and control groups, across age groups, grazing areas, or farms. Except for the most exposed children (10% percentile), the estimated annual effective dose to adults and children from 210 Po ingestion in black and healthy livers remained below the world average of 120 µSv due to the ingestion of naturally occurring radionuclides. The overall prevalence of ovine acquired melanosis based on a large sample size was 10.59%, with herd prevalence ranging from 0% to 51.79%. Age-specific prevalence was 10.38% in lambs and 13.40% in adult sheep. Acquired melanosis was negatively correlated with fat and muscle content in carcasses. The consumption of sheep livers from South Greenland does not appear to pose a toxicological or radiological risk. Graphical Abstract